Markers of bone turnover in bone metastases - Litwiniuk, Maria; Kopczyński, Zygmunt (Contemporary Oncology/Współczesna Onkologia, 2002)
The skeleton is a common site for metastases in patients with malignancies, especially with breast and prostate cancer. The diagnosis of bone metastases can be difficult. The screening for bone metastases is based on radioisotopic bone scans, confirmed by supplemental radiographic bone surveys. Scintigraphy is simple, can examine the whole skeleton and is sensitive but lacks specificity. Changes of bone scintigraphy uptake is difficult to interpret because scintigraphy detect not only the osteoblastic metastatic lesions but also the healing process of bone metastases. Conventional radiology plays a central role in the diagnosis of metastases but is less sensitive and radiological changes in bone metastases are very slow. Elevation of tumor associated markers (CA 15.3 in breast and PSA in prostate cancer) can be an early sign of metastatic disease and bone matastases. In recent years new biochemical markers of bone remodeling hold great promise because of their relatively sensitivities and specificities. Markers of bone turnover could help the clinician in the early diagnosis of bone metastases. They correlate with presence of bone metastases and extend of bone disease, but there are no laboratory findings which are pathognomonic for skeletal metastases with possible exception of BALP in prostate carcinoma. Bone markers can be used for monitoring patients especially when bone is the only site of metastases. Bone resorption markers may be useful for follow-up bisphosphonate therapy. The use of biochemical markers of bone turnover to monitor therapy is not suggested for routine care. More studies are necessary to determine usefulness of bone markers in oncology.